Gap Analysis between the Current and Desired states of Talent Management Programs and Determination of Improvement Priorities by using Importance-Performance Analysis (IPA) - Abdolali Keshtegar (Journal of Global Pharma Technology, 2018)
Today, talent management is one of the main areas of human resources management for gaining competitive advantage and it is essential for organizations to examine systematically the status of their talents and take steps in order to enhance the situation. Given the importance of this subject, the present study aims to conduct a gap analysis between the current and desired states of talent management and also determine the improvement priorities using the Importance-Performance analysis (IPA). This study is a descriptive survey and the statistical population consists of all staff of the department of education in the city of Birjand in Iran. A sample size including 86 people was determined. In this study, two researcher-made questionnaires were used in order to achieve the research goals. After the confirmation of validity and reliability, these two questionnaires were distributed among the respondents and finally, 76 questionnaires were collected and studied. The gathered data were analyzed by means of SPSS statistical analysis software and based on the IPA model. The results of this study showed that there was a significant gap between the current and optimal states of talent management, and this gap was present in all four main dimensions of the research and all factors. According to the IPA model, the eight following factors were determined as improvement proprieties: Adjustment of salaries of employees with their activities, planning to prepare right people for filling key roles, harmony between the post and people who are selected for it, the existence of the sense of success and progress in the organization, continuous evaluation of staff performance and identifying their weakness and strengths, modifying undesirable behaviors, actively creating equal development opportunities for employees, coaching and educating prominent and professional people. According to the existing gap and given that the improvement priorities are of all four dimensions of talent management, it is thus recommended to focus on all four aspects for improving the situation and in case of restrictions, it is recommended to put the aforementioned determined improvement priorities at the top of improvement programs in the short term.Key Words: Gap analysis, Talent Management, Determination of Improvement Priorities.